Application of curriculum design maturity model at private institution of higher learning in Malaysia: a case study - Chee, Ling Thong; Jusoh, Yusmadi Yah; Abdullah, Rusli; Alwi, Nor Hayati (Springer Netherlands (SpringerLink), 2013)
Capability Maturity Model (CMM) is applied as a process improvement model not only in software industry but also in education sector. This study proposes a maturity model, which constructed based on CMM, in guiding curriculum designers in Institution of Higher Learning (IHL) in Malaysia to design quality curriculum. The proposed maturity model possesses process and product elements; and it contains a set of key process areas and best practices. A case study is carried out in a private IHL in Malaysia to perform a pilot test on the proposed maturity model. The results may also help the institution to be informed of current as well as future improvement process, finally aid in producing quality curriculum for IHL in Malaysia.